2003
DOI: 10.1590/s0100-204x2003000400014
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting attack rate of whitefly on the eggplant

Abstract: The objective of this study was to determine the effects of weather, predators and parasitoids, canopy height and plant age, leaf chemical composition, levels of leaf N and K and leaf trichomes on the intensity of Bemisia tabaci attack on Solanum melongena. A higher density of nymph and whitefly adults was recorded at the base and medium of the plant compared to the apex. A higher number of eggs was observed on the medium part than on the apical and base part of the plants dossel. An increase in the density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Feeding of whiteflies may vary depending on the angle of trichome to the leaf surface, as well as varying based on leaf color, length, and plant variety [73]. Leite et al [74] reported a non-occurrence of oviposition by B. tabaci on the apical leaves of eggplant with high trichome density. A significant negative correlation between the number of leaf hairs per unit area and whitefly count has also been reported in pumpkin [75].…”
Section: Physical Basis Of Resistancementioning
confidence: 99%
“…Feeding of whiteflies may vary depending on the angle of trichome to the leaf surface, as well as varying based on leaf color, length, and plant variety [73]. Leite et al [74] reported a non-occurrence of oviposition by B. tabaci on the apical leaves of eggplant with high trichome density. A significant negative correlation between the number of leaf hairs per unit area and whitefly count has also been reported in pumpkin [75].…”
Section: Physical Basis Of Resistancementioning
confidence: 99%
“…Nutritional and morphological features, organic compound levels, and natural enemies do not explain the highest density of B. tabaci on eggplant because none of these characteristics are unique for these plants. The highest occurrence of B. tabaci in eggplant can be due to planting time because the warmer periods of the year were positively correlated with this pest in most crops (r = 0.49, P = 0.0000) as found by Leite et al (2003). This agrees with the survival rate of 88.7, 60.2, 67.5, 46.4, and 45.8% of B. argentifolii juveniles on S. melongena, L. esculentum, Ipomoea batatus (L.), C. sativus, and P. vulgaris, respectively (Tsai and Wang, 1996).…”
Section: Discussionmentioning
confidence: 75%
“…Nontheless, there are some reports about some species of the genus feeding on aleyrodids e.g., Exochomus bimaculosus Mulsant which feeds on Bemisia tabaci (Gennadius) (Yigit 1992, Leite et al 2003, Hodek and Honěk 2009). …”
Section: Resultsmentioning
confidence: 99%